2022
DOI: 10.1111/faf.12650
|View full text |Cite
|
Sign up to set email alerts
|

Strength and consistency of density dependence in marine fish productivity

Abstract: The correct prediction of the shape and strength of density dependence in productivity is key to predicting future stock development and providing the best possible long-term fisheries management advice. Here, we identify unbiased estimators of the relationship between somatic growth, recruitment and density, and apply these to 80 stocks in the Northeast Atlantic. The analyses revealed density-dependent recruitment in 68% of the stocks. Excluding pelagic stocks exhibiting significant trends in spawning stock b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 70 publications
1
20
1
Order By: Relevance
“…Numerous instances of competing species and techniques for mathematical modelling are discussed in one of the pioneering publications on interspecific interaction [55]. The scramble competition has been found to fit the Ricker model [56,57]. From order to chaos, the Ricker model illustrates dynamics…”
Section: Ricker's Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…Numerous instances of competing species and techniques for mathematical modelling are discussed in one of the pioneering publications on interspecific interaction [55]. The scramble competition has been found to fit the Ricker model [56,57]. From order to chaos, the Ricker model illustrates dynamics…”
Section: Ricker's Modelmentioning
confidence: 99%
“…Ricker's model is often used to explain the dynamics of two populations that are linked through migrations [50][51][52][53][54][55][56][57][58]. As a result, nothing is known about how Ricker communities evolved.…”
Section: Ricker's Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Cannibalism is known to be frequent in fish populations, is the most straightforward process of over-compensatory mortality and was the core hypothesis of development of Ricker historical stock and recruitment theory (Ricker, 1954). Moreover, Rindorf et al (2022) recently showed that most of exploited stocks undergo density-dependence before recruitment and that overcompensation was more likely to occur in demersal stocks such as the Bay of Biscay of sole.…”
Section: Discussionmentioning
confidence: 99%